A 2540-year record of moisture variations derived from lacustrine sediment (Sasikul Lake) on the Pamir Plateau. (July 2014) - Lei, Yanbin; Tian, Lide; Bird, Broxton W; Hou, Juzhi; Ding, Lin; Oimahmadov, Ilhomjon; Gadoev, Mustafo
Although the Pamir Plateau is an ideal place to investigate paleo-environmental changes in the westerlies-dominated high Central Asia, there are only few Holocene records from this region. We present a sub-centennially resolved lacustrine record of moisture variations from Sasikul Lake, central Pamir Plateau, based on geochemical, sedimentological, and mineralogical proxies. Our results show that generally dry conditions at Sasikul Lake during the past 2540 years were interrupted by a pronounced wet period betweenad 1550 and 1900, corresponding to the 'Little Ice Age' (LIA). More negative values of carbonate δ 18 O, lower total inorganic carbon (TIC) and sand content during the LIA all indicate a relatively wet period with higher lake level. Higher TIC during the 'Medieval Warm Period' (MWP;ad 950–1200) reveals a lower lake level relative to the LIA. Low δ 18 O during this time is probably attributed to changes in the isotopic composition of input water and/or upstream moisture sources. The significant increase in detrital minerals and decrease in carbonate during the LIA provide further evidence for higher allochthonous input during the wet period at Sasikul Lake. The inferred moisture variations are consistent with existing records from regions of the northern Tibetan Plateau and Central Asia that are also influenced by the westerlies, but out-of-phase with those records from the Asian monsoon region, indicating that moisture variations at Sasikul Lake were mainly influenced by the strength and trajectories of the westerlies. The inferred water level at Sasikul Lake decreased significantly during the first half of the 20th century, and then increased in recent decades. This is consistent with the increase in lake area derived from satellite images and the monitoring data of large lake-level changes in Central Asia.